2007
DOI: 10.1007/s00464-007-9709-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of laparoscopic adrenalectomy for adrenal tumours of 6 cm or greater

Abstract: In the absence of local invasion, the outcomes of laparoscopic adrenalectomy for patients with tumours >/=6 cm were comparable to those with tumours <6 cm. This has helped confirm a policy of initial laparoscopic resection for all noninvasive adrenal tumours can be applied safely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 19 publications
5
57
0
3
Order By: Relevance
“…In the series of Parnaby and colleagues (16), pathological evaluation of 101 patients demonstrated benign lesions in 70, nonfunctional adrenal tumors in 5, adrenal carcinoma in 17, metastatic adrenal carcinoma in 3, contralateral adrenal metastasis in 3, retroperitoneal sarcomas in 2 and mixed type adenoma in 1 patients. Zakarias et al (17) reported similar pathological results in another laparoscopic adrenalectomy series of 52 patients.…”
Section: Discussionmentioning
confidence: 96%
“…In the series of Parnaby and colleagues (16), pathological evaluation of 101 patients demonstrated benign lesions in 70, nonfunctional adrenal tumors in 5, adrenal carcinoma in 17, metastatic adrenal carcinoma in 3, contralateral adrenal metastasis in 3, retroperitoneal sarcomas in 2 and mixed type adenoma in 1 patients. Zakarias et al (17) reported similar pathological results in another laparoscopic adrenalectomy series of 52 patients.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, unpredicted adhesions of the mass undetectable in CT or MR to surrounding tissues may be another reason necessitating conversion to open surgery. Parnaby et al [23] indicated that in patients undergoing surgery with the indication of pheochromocytoma, probability of conversion to open surgery was higher. Even though contrary opinions have been advocated in the literature, higher body mass index is a risk factor necessitating conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the largest tumor diameter was 8.5 cm, which posed no problems during surgery, since the imaging studies conducted had ruled out local infiltration or of adjacent organs. A study comparing the role of laparoscopic adrenalectomy to open surgery in tumors less than or greater than 6 cm concluded that results are similar in the absence of local invasion 8 . Similarly, when a correct preoperative assessment is performed, the possibility of intraoperative complications decreases.…”
Section: Discussionmentioning
confidence: 99%